Fitness profile and training of Special Operation Forces: a comparison with sports athletes - Dössegger, Alain; Gsponer, Thomas; Flück, Martin; Protte, Christian; Wyss, Thomas; Häusler, Eric; Gerber, Markus; Faude, Oliver (Frontiers in Sports and Active Living, 2025)
IntroductionTactical athletes of Special Operations Forces personnel face diverse, high-risk demands—from explosive power actions and maximal strength tasks to prolonged endurance efforts and rapid decision making under stress. This study aimed to develop a multidimensional fitness profile for these tactical athletes by defining Critical Success Factors and translating them into measurable performance indicators, then comparing Swiss Special Operations Forces operators and candidates with sports athletes.MethodIn a cross sectional, observational design, 262 male participants completed a tailored battery of laboratory and field tests: 69 Special Operations Forces operators, 175 Special Operations Forces candidates, and 18 athletes from disciplines such as decathlon, Thai boxing, wrestling, and ice hockey. Practitioner interviews established key mission critical factors, which were operationalized into tests of reaction time, power, strength, severe intensity muscular and cardiopulmonary work capacity, and aerobic endurance. To evaluate group and unit effects, we compared two Bayesian linear regression models: a baseline model (m₀) and a model (m₁) that included group as a fixed factor. Evidence for a group effect was quantified by the Bayes Factor and Probability of direction, where >90% is considered equal to an alpha level of 0.05, thus a non-negligible effect.ResultsWeekly training volume averaged 8.5 h for operators, 6.9 h for candidates, and 9.5 h for athletes. SOF operators and candidates demonstrated fitness levels comparable to sports athletes. Mean jumping distance was 2.43 m, relative hand-grip strength 1.51 kg/kg body mass, deadlift with 100 kg was 20 repetitions, and maximal oxygen uptake measured 54 ml/kg/min. Candidates recorded faster computer based reaction times than operators, while operators outperformed candidates and athletes in a close-quarters combat simulation. Both candidates and operators completed fewer 100 kg deadlift repetitions compared to the mean of the athletes.DiscussionSwiss Special Operations Forces operators and candidates demonstrate fitness profiles on par with sports athletes across multiple domains, validating their designation as tactical athletes. The normative values and test battery offer a tool for identifying individual strengths and weaknesses, guiding targeted training programs, and informing selection and readiness assessments. Future research should explore longitudinal interventions and predictive models of operational performance.